A Rare Finding of Clear Cell Papillary Renal Cell Carcinoma in a Complex Renal Cyst - K. P., Dr Suneetha; Javali, Dr Dilip; J., Dr Gayathri (International Journal of Innovative Research in Medical Science, 2019)
Multilocular cystic renal cell carcinomas (RCC’s), Unilocular cystic RCC’s and RCC’s with extensive cystic necrosis and unilocular cysts with mural tumor nodules forms a wide category of RCC’s. Cystic RCC’s represent upto 3-14% of all RCC’s.[1] Here we present a case of 68 year old female who is a known case of DM, hypothyroidism, bronchial asthma presenting with complains of pain abdomen since 1 year. She has been a case of renal TB and on ATT 30 years ago. Further the patient was evaluatedand foundto have a small partly exophytic cortical cyst measuring 13x12mm noted in the inter polar region posteriorly along with multiple well defined hyper dense non enhancing cortical and exohytic cysts notes in upper / lower and inter polar regions, largest measuring 1.8x1.7cms in upper pole suggestive of hemorrhagic cysts. A diagnosis of left renal complex cyst was made. Alaporoscopic left partial cystectectomy was done and sent for histopathological examination. Microscopy revealed Cystic clear cell fgv Renal cell carcinoma, Furhman Grade 1(Low grade) within a 0.1cm thickening which was further confirmed with IHC expressing strongly for CK7,PAX8 and CAIXand confirmed the diagnosis as Clear cell Papillary Renal cell carcinoma. Patient is being followed up and no recurrence / metastasis has been reported. This provides us an opportunity to consider an unusual finding of Clear Cell Papillary RCC in a complex renal cyst and to look into the cystic lesion with more importance helping us in avoiding missing a carcinoma as found in the present case.